The neurocognitive mechanism linking temperature and humidity with miners’ working memory: an fNIRS study - Tian, Chenning; Li, Hongxia; Tian, Shuicheng; Tian, Fangyuan; Yang, Hailan (Frontiers in Human Neuroscience, 2024)
Background: In China's coal mines, employees work in environments reaching depths of 650 meters, with temperatures around 40°C and humidity levels as high as 90%, adversely affecting their health, safety capabilities, and cognitive functions, especially working memory. This study aims to explore different temperature and humidity conditions' impact on neurocognitive mechanisms to enhance occupational health and safety.Methods: This study, conducted between June and August 2023, with 100 coalmine workers from the Hongliulin Mining Group, utilized functional near infrared spectroscopy (fNIRS) and short-term visual memory tasks to evaluate the effects of high temperatures and humidity on working memory by monitoring activity in the cerebral cortex. Behavioral data, and neurophysiological data were analyzed using Tukey's HSD for significant differences and multiple regression to explore the impact of temperature and humidity. The β-values of Oxy-Hb for different regions of interest were calculated using General liner model (GLM), and the activation maps were plotted by NIRS_KIT.Results: High temperature and humidity (Condition IV) significantly depressed reaction times and working memory compared to other conditions, with temperature having a more pronounced impact than humidity on these cognitive measures (p<0.05). Oxy-Hb concentration increased notably under Condition IV, emphasizing temperature's influence on brain oxygen levels. ROI analysis revealed varied brain activation patterns; The activation of ROI A and B (prefrontal cortex) increased with the increase of temperature and humidity, while ROI C (supplementary motor area) was less sensitive to temperature, indicating the complex influence of environmental factors on brain function.Conclusion: This study highlights the important effects of temperature and humidity on cognitive performance and brain function, highlighting the need to optimize the environment of miners' sites to improve productivity and safety.